Rancang Bangun Aplikasi Perencanaan Anggaran Biaya Tenaga Kerja Pada Proyek Konstruksi Gedung - Muzaki, Farouk Kusdony; Widodo, Arifin Puji; Romeo, Romeo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Construction project management planning will require manpower requirements, the calculation of labor cost budget, number of employees, the arrangement of activities and time required to complete each activity. So far, only managing assessments of workforce needs. This is because of the experience and do not know the technical calculations in calculating labor costs. As a result, the project failed and declining consumer confidence.Handling solutions to create budget planning application labor costs in building construction projects. The system is built to calculate the labor requirements, needs labor costs, and time required to complete the project.This application generates information report labor cost budget plan, the amount of manpower needs, and schedulling of the project. Based on the result of experiments performed, the application can help the process of planning manpower requirements, and planning labor costs in building construction projects.